Correlation of geoelectric data with aquifer parameters to delineate the groundwater potential of hard rock terrain in Central Uganda. - Batte, A.G.; Barifaijo, E.; Kiberu, J.M.; Kawule, W.; Muwanga, A.; Owor, M.; Kisekulo, J. (My University, 2010)
Knowledge of aquifer parameters is essential for management of groundwater resources. Conventionally, these parameters are estimated through pumping tests carried out on water wells. This paper presents a study that was conducted in three villages (Tumba, Kabazi, and Ndaiga) of Nakasongola District, central Uganda to investigate the hydrogeological characteristics of the basement aquifers. Our objective was to correlate surface resistivity data with aquifer properties in order to reveal the groundwater potential in the district. Existing electrical resistivity and borehole data from 20 villages in Nakasongola District were used to correlate the aquifer apparent resistivity (ρ e) with its hydraulic conductivity (K e), and aquifer transverse resistance (TR) with its transmissivity (T e). K e was found to be related to ρ e by; [Math Processing Error]. Similarly, TR was found to be related to T by; [Math Processing Error]. Using these expressions, aquifer parameters (T c and K c) were extrapolated from measurements obtained from surface resistivity surveys. Our results show very low resistivities for the presumed water-bearing aquifer zones, possibly because of deteriorating quality of the groundwater and their packing and grain size. Drilling at the preferred VES spots was conducted before the pumping tests to reveal the aquifer characteristics. Aquifer parameters (T o and K o) as obtained from pumping tests gave values (29,424.7 m2/day, 374.3 m/day), (9,801.1 m2/day, 437.0 m/day), (31,852.4 m2/day, 392.9 m/day). The estimated aquifer parameter (T c and K c) when extrapolated from surface geoelectrical data gave (7,142.9 m2/day, 381.9 m/day), (28,200.0 m2/day, 463.4 m/day), (19,428.6 m2/day, 459.2 m/day) for Tumba, Kabazi, and Ndaiga villages, respectively. Interestingly, the similarity between the K c and K o pairs was not significantly different. We observed no significant relationships between the T c and T o pairs. The root mean square errors were estimated to be 18,159 m2/day and 41.4 m/day.
Keywords: Basement complex, transverse resistance, hydraulic conductivity, groundwater, electrical resistivity methods,Uganda